Aristotelian Concept of “Therapeutic” Function of Tragedy with the Example of Sophocles’ “Theban Plays” (Oedipus the King, Oedipus at Colonus, Antigone) - Kieliszek, Zdzisław; Gocłowska, Ewa (Studia Warmińskie, 2018)
The article is dedicated to the comparative analysis of the concept of ideal tragedy presented by Aristotle in Poetics, and the works of Sophocles forming the “Theban Plays” (Oedipus the King, Oedipus at Colonus and Antigone). The article depicts the most important accomplishments of Sophocles to start with. Afterwards, Aristotle has been presented as the creator of the ideal model of tragedy. Further, the Aristotelian concept of catharsis, which is the key element of his vision of ideal tragic works, and corresponding with it constructs of the plot and the figures’ characters have been comparatively shown. On the basis of the analysis one can reach a conclusion that Aristotle named and systematised the rules which Sophocles had been using at the theatre stage with the aim of the spectators experiencing catharsis, in other words, evoking and purging the spectators of the feelings of pity and terror. Moreover, it turns out that in the Aristotelian theory, as well as in the works of Sophocles, the layout of events creating the plotline is related to the feeling of pity, whereas suitably built characters are related to pity.